Energy and sustainable development in Mexico - Moroney, John R. (Texas A & M University economics series ;, 2005)
"The authors assess Mexico's goals of sustainability and the major policy changes that will be required to achieve them. Although their analysis of Mexico's energy sector is based on rigorous econometric models, the book will be of interest to all readers concerned with Mexican economic development and its prospects for the future."--Jacket.